Exogenously applied muscle metabolites synergistically evoke sensations of muscle fatigue and pain in human subjects - Pollak, Kelly A.; Swenson, Jeffrey D.; Vanhaitsma, Timothy A.; Hughen, Ronald W.; Jo, Daehyun; Light, Kathleen C.; Schweinhardt, Petra; Amann, Markus; Light, Alan R. (Experimental physiology, 2014)
New Findings What is the central question of this study? Can physiological concentrations of metabolite combinations evoke sensations of fatigue and pain when injected into skeletal muscle? If so, what sensations are evoked? What is the main finding and its importance? Low concentrations of protons, lactate and ATP evoked sensations related to fatigue. Higher concentrations of these metabolites evoked pain. Single metabolites evoked no sensations. This suggests that the combination of an ASIC receptor and a purinergic P2X receptor is required for signalling fatigue and pain. The results also suggest that two types of sensory neurons encode metabolites; one detects low concentrations of metabolites and signals sensations of fatigue, whereas the other detects higher levels of metabolites and signals ache and hot. The perception of fatigue is common in many disease states; however, the mechanisms of sensory muscle fatigue are not understood. In mice, rats and cats, muscle afferents signal metabolite production in skeletal muscle using a complex of ASIC, P2X and TRPV1 receptors. Endogenous muscle agonists for these receptors are combinations of protons, lactate and ATP. Here we applied physiological concentrations of these agonists to muscle interstitium in human subjects to determine whether this combination could activate sensations and, if so, to determine how the subjects described these sensations. Ten volunteers received infusions (0.2 ml over 30 s) containing protons, lactate and ATP under the fascia of a thumb muscle, abductor pollicis brevis. Infusion of individual metabolites at maximal amounts evoked no fatigue or pain. Metabolite combinations found in resting muscles (pH 7.4 + 300 nm ATP + 1 mm lactate) also evoked no sensation. The infusion of a metabolite combination found in muscle during moderate endurance exercise (pH 7.3 + 400 nm ATP + 5 mm lactate) produced significant fatigue sensations. Infusion of a metabolite combination associated with vigorous exercise (pH 7.2 + 500 nm ATP + 10 mm lactate) produced stronger sensations of fatigue and some ache. Higher levels of metabolites (as found with ischaemic exercise) caused more ache but no additional fatigue sensation. Thus, in a dose‐dependent manner, intramuscular infusion of combinations of protons, lactate and ATP leads to fatigue sensation and eventually pain, probably through activation of ASIC, P2X and TRPV1 receptors. This is the first demonstration in humans that metabolites normally produced by exercise act in combination to activate sensory neurons that signal sensations of fatigue and muscle pain.